Ensino do handebol em longo prazo : estudo a partir da opiniao de treinadores - Menezes, Rafael Pombo (2018)
The aim of this work was to investigate the preference/use of teaching approaches of handball coaches in four teams (under-12, under-14, under-16 and under-18). Six coaches of Sao Paulo State were interviewed (semistructured instrument). The method of Collective Subject Discourse was adopted for speech analysis, which allowed us to explore the central ideas (qualitative analysis). The results pointed out particularities among the coaches' opinions when comparing with some models proposed. It is noteworthy the presence of the traditional approach in under-12 teams, the presence of the global-functional method (teaching through games) in all teams and a growing preference/use regarding the situational method. It was concluded that the results showed specific characteristics of a group of coaches from the State of Sao Paulo, which revealed an important research field related to handball teaching
O objetivo deste estudo foi investigar a preferência/utilização dos métodos de ensino por treinadores de handebol em quatro categorias (sub-12, sub-14, sub-16 e sub-18). Para isso foi elaborado um instrumento de entrevista semiestruturada e aplicado a treinadores do Estado de São Paulo. O Discurso do Sujeito Coletivo foi o método adotado para a tabulação e análise dos discursos, o que permitiu explorar as ideias centrais também em termos quantitativos. Os resultados apontaram particularidades entre as opiniões dos treinadores quando comparadas a alguns modelos descritos na literatura. Destaca-se, especialmente, a presença do método analítico-sintético na categoria sub-12, a presença do método global-funcional em todas as categorias e a crescente preferência/utilização referente ao método situacional. Conclui-se que os resultados apontaram características específicas a um grupo de treinadores do Estado de São Paulo, revelando um importante campo de investigação no âmbito do ensino do handebol
Keywords: Teaching; Coaching; Sport formation; Handball; Ensino^lpt; Treinadores; Formação esportiva; Handebol; Enseñanza; Entrenadores deportivos; Juegos de pelota